Postharvest quality of conventionally and organically grown banana fruit - Caussiol, Laure (Cranfield University, 2001)
Quality is increasingly important for retailers, who tend to look for more definitive assessment criteria. Taste has become a major issue over past years for consumers, who are seeking higher quality produce. For banana fruit, at least one major retailer is asking TSS measurement in addition to the usual assessment based on skin colour. At the same time organic produce sales are increasingly important for ripeners and retailers to consumers. This study investigated variability in banana pulp with regard to sampling position from proximal, middle and distal portions. Also two different devices, the traditional pocket refractometer and the digital refractometer were evaluated. TSS was measured on juice obtained directly from the pulp, as practised by one supermarket representative, versus the more conventional method of homogenizing pulp samples in distilled water. Finally, a comparison of postharvest qualities of conventionally and organically grown banana fruit from nearby plantations in the Dominican Republic was made. This comparison involved several harvest times over the seasonal period from February to June 2001. Green mature Cavendish bananas var. Grand Nain were imported from the Dominican Republic by SH Pratt’s & Co. (Luton, UK). Both the conventionally and the organically grown bananas from the same area were held at about 15 degrees C during shipping and handling. The fruit were then ripened in a postharvest laboratory in the UK with a shot of 100 muL/L ethylene applied for 48 hours at 20 ±1 degree C. They were then assessed over 12 days of shelf life at this same temperature and at 60 ±10 % relative humidity. Fruit weight (g), colour (L* and H degrees), acidity (ml of 0.1 N NaOH), firmness (N) and TSS (%Brix) were assessed every second day during shelf life. In addition, starch breakdown was visualised by dipping slices of banana in iodine solution. Sensory analysis on the ripened fruit was also made with 30 panellists for four out of six of the harvest times.